2022
DOI: 10.1371/journal.pone.0267848
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of depression and anxiety among Chinese diabetic retinopathy patients: A cross-sectional study

Abstract: The purposes of this study were to evaluate the mental health among patients with diabetic retinopathy (DR) and to explore its’ influencing factors. A cross-sectional survey was conducted in Liaoning Province, China. A total of 200 patients volunteered to participate in the survey. Psycho-social variables included stress, self-efficacy, resilience, and social support. logistic regression analysis was used to explore the effect of psycho-social factors on depression and anxiety in DR patients. The prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 53 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…The participants in this study may have exaggerated their illnesses because of their visual impairment and concerns about blindness, which may have led to a variety of negative emotions. Previous studies have demonstrated that the overall mental health status of patients with DR patients is low (Xu et al, 2022). Chinese medical institutions should direct more attention to the high prevalence of depression (25.0%) and anxiety (13.5%) in these patients (Xu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants in this study may have exaggerated their illnesses because of their visual impairment and concerns about blindness, which may have led to a variety of negative emotions. Previous studies have demonstrated that the overall mental health status of patients with DR patients is low (Xu et al, 2022). Chinese medical institutions should direct more attention to the high prevalence of depression (25.0%) and anxiety (13.5%) in these patients (Xu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the overall mental health status of patients with DR patients is low (Xu et al, 2022). Chinese medical institutions should direct more attention to the high prevalence of depression (25.0%) and anxiety (13.5%) in these patients (Xu et al, 2022). This study found that the suffering of the respondents was more serious than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…The close association between many retinal diseases and psychosomatic diseases may be related to the patients’ reduced visual function ( Moschos et al, 2015 ; Vu et al, 2021 ), self-assessment of health and quality of life due to the condition ( Vu et al, 2021 ), and dependence on family caregivers ( Jin et al, 2021 ). In addition, high mental stress ( Xu et al, 2022 ), low income and living alone ( Chen et al, 2018 ) are all risk factors for eye disease associated with psychosomatic disease, but increased social support has a significant protective effect on such patients ( Xu et al, 2022 ). Negative emotions such as anxiety and depression can further exacerbate the progression of eye disease and anxiety reportedly increases the risk of glaucoma progression ( Shin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, neovascular age-related macular degeneration is reported in 26.9% of patients with symptomatic depression and 25.5% with symptomatic anxiety ( Fernandez-Vigo et al, 2021 ), and depressive symptoms are even more common than anxiety symptoms ( Dawson et al, 2014 ). Among patients with diabetic retinopathy (DR), 25% suffer from depression and 13.5% suffer from anxiety ( Xu et al, 2022 ). The incidence of DR is reduced after the use of antidepressants ( Yekta et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, earlier disease detection and DR prevention are made possible by improved diabetes diagnosis and management D standards. Potential psychological stress may accelerate the progression of DR through biological pathways (9) or through behavioral pathways (10), which can result in poor blood sugar control and increase the risk of DR. On the other hand, psychological factors are significantly related to the occurrence and development of DR (11), active diabetes health management, psychological intervention, and DR can be slowed down (12). In order to prevent and treat visual impairment as well as manage diabetes holistically, it is important to pay attention to psychological aspects and their underlying mechanisms and to act quickly.…”
Section: Epidemiology Of Diabetic Retinopathymentioning
confidence: 99%